Mechanisms underlying social gradients in child and adolescent antisocial behaviour - Patrycja J. Piotrowska; Christopher B. Stride; Barbara Maughan; Richard Rowe (Elsevier, 2019)
Objective: A number of studies demonstrate a social gradient in behavioural problems, with children from low-socioeconomic backgrounds experiencing more behavioural difficulties than those from high-socioeconomic families. Antisocial behaviour is a heterogeneous concept which includes diverse behaviours such as physical fighting, vandalism, lying, disobedience and irritability. It remains unclear whether the mechanisms underlying social inequalities are similar across these different subtypes of antisocial behaviour. This study aimed to simultaneously test a range of individual, family and neighbourhood factors as mediators of the relationship between income and subtypes of antisocial behaviour. Method: Data on a UK representative sample of 7977 children and adolescents, aged 5-16, was analysed in a series of nested structural equation models. A range of antisocial outcomes, including irritability, aggression, and callous-unemotional traits, were measured. Income quintiles were used to indicate family socioeconomic status. A range of potentially mediating or confounding variables, such as family functioning and parental mental health, were also measured. Results: Analyses revealed that unhealthy family functioning, neighbourhood disadvantage, stressful life events and children's literacy difficulties were mediating variables contributing to the indirect effect of income on a range of antisocial behaviours. Conclusion: As expected family functioning accounted for a substantial proportion of the association between SES and antisocial behaviour, we also found evidence that child cognitive functioning might perform an important role. Our findings emphasise the importance of addressing the mechanisms underlying the association between SES and behavioural problems. Keywords: socioeconomic status, antisocial behaviour, social gradient, mediators, family